Perlindungan Hukum Soft-dat, Terhadap Plagiarisme - Budianto, Agus (LAW REVIEW, 2006)
Copyright is one of the intellectual which is protected by law, national and international. Copyright allows authors to make money off of their labor (economic right). It prevents others from taking there work for free. It also prevents people from altering the work without permission (moral right). Because of development of technology information, one can also easly get information from internet or web and use it for their own activities. Everybody has to know plagiarism and the Internet has dramatically increased the ease of and opportunities for plagiarism. "Cyber-plagiarism " is the term used to describe the process by which lecturer and students either copy ideas found on the Web without giving proper attribution and to copying by optical disc.